Profile of biology teachers implications for in-service teacher training - Paris, Peter Ernie D. (2006)
This study sought to identify the unique characteristics of an effective biology teacher based on the perception of biology teachers themselves, and to utilize the constructed profile to determine the existing current teaching effectiveness of biology teachers based on student evaluation. The first phase of the study involved establishing the benchmark characteristics of an effective biology teacher based on their own perception; second was an assessment of their effectiveness based on their students; and third was determining impediments on effective biology teaching as identified by teachers subjected to case studies. Based on the benchmark characteristics given, the students deemed their biology teachers as generally effective while there were still some who are just moderately effective. The main problem in teaching biology effectively is that different teaching strategies are seldom applied in the course due mainly to financial constraints.
"March 2006."
Thesis (M.A. Education : Biology Education)--University of the Philippines Diliman.
Keywords: Biology teachers -- Philippines -- Western Visayas; Biology teachers -- In-service training -- Philippines -- Western Visayas; Biology teachers -- Rating of -- Philippines -- Western Visayas; Teacher effectiveness -- Philippines -- Western Visayas